(untitled) (CAHIERS MAGELLANES-NS, 2024)
To extract the phyto-compounds of pharmaceutical importance present in selected herbal leaves. The medicinal plant used for the analysis purpose is Aloevera. Aloevera is having many medicinal properties like healing the burns, curing the cold and for face it acts a best moisturizer and many more. Near infrared reflectance spectroscopy analysis was performed using a Shimadzu (Japan) UV-NIR-3600 Equipped with PMT (photomultiplier tube) for the ultraviolet and visible regions. The Leaf samples were placed in rotating sample cup, and scanned on reflectance mode in the spectral range from 4,000 to 12,500 cm−1 at room temperature (∼20 ◦C). In each of the reflectance measurements, 64 scans were run and the resolution used for spectral analysis was 8 cm−1. Background corrections were made before each sample was scanned. Samples were measured in triplicate, which increased the scanned surface of samples for reducing errors. The spectral absorbance values were recorded as log1/R, where R is the sample reflectance. Phyto-compounds can be found by so many extraction methods and solvents depending on the nature of the compound we are looking for. Every leaf is having a medicinal quality but the concept is that we are not aware of that. How many of us know that babul tree has galactagogue properties? But still in India we think that it drains the ground water and we cut the tree. The main origin of the work started with the basic findings of medicinal properties present in herbal leaves.Here we are using image processing techniques, which makes easier for the identification of phyto-compounds. For this we have chosen some herbal leaves such as tulasi, aloe-vera which are plenty in our surroundings and also have so many health benefits by using. Manual interpretation of herbal leaves which have good sufficient amounts of phyto compounds that are useful in the preparation of Ayurvedic medicines and have good health benefits leads to error. So, it is essential to develop an automatic system for the identification of amount of phyto compounds to avoid the errors. A digital image capturing is proposed to acquire various images of different herbal leaves and they are used to develop a database for the comparison with spectral analysis values obtained using UV visible NIR spectroscopy. The novelty of the work is that comparative analysis using analytical and digital method are determined. In pharmaceutical industries the work can be applied for classifying the leaf based on its medicinal properties.